Determination of triacylglycerol regioisomers using differential mobility spectrometry - Sala, Martin; Lísa, Miroslav; Campbell, J. Larry; Holčapek, Michal (John Wiley & Sons Ltd., 2016)
RATIONALE: Triacylglycerols (TG) contain three fatty acyls attached to the glycerol backbone in stereochemically numbered positions sn-1, 2 and 3. Isobaric TG with exchanged fatty acyl chains in positions sn-1/3 vs. sn-2 are referred to as regioisomers and the determination of their regioisomeric ratios is important for nutrition purposes. METHODS: Differential mobility spectrometry (DMS) coupled to electrospray ionization mass spectrometry (ESI-MS) is applied for the separation of simple unsaturated TG regioisomers extracted from porcine adipose tissue using their silver-ion molecular adducts. RESULTS: Four pairs of TG regioisomers containing combinations of unsaturated and saturated fatty acyl chains are successfully separated using DMS with 1-butanol or 1-propanol as the chemical modifier. Various experimental parameters are carefully optimized, such as the separation and compensation voltages applied to DMS electrodes, the type and flow rate of chemical modifier and the dwell time of analyte ions in the DMS cell. The optimized DMS approach is used for the characterization of TG regioisomers in less than one minute, compared to tens of minutes typical for silver-ion or reversed-phase high-performance liquid chromatography/mass spectrometry approaches. CONCLUSIONS: The application of this method for the characterization of TG regioisomers in porcine adipose tissue shows the method suitability for analyses of other animal fats.
Stanovení regioisomerů trigliceridů pomocí MDS
Keywords: ionization mass-spectrometry; performance liquid-chromatography; silver-ion; fatty-acids; isomeric triacylglycerols; structural elucidation; positional isomers; phase; separation; oils; DMS; ESI-MS; TG